Aquaculture production systems - Tidwell, James H. (Wiley-Blackwell, 2012)
Provides a valuable survey of key production systems that will allow the reader to better understand how aquaculture depends upon and interacts with its environment. * Looks at a variety of systems currently used in the production of shellfish and finfish. These systems range from low input methods to super-intensive systems